Isolation and screening of lactic acid bacteria (LAB) from non-broiler chicken (Gallus gallus) for potential probiotic - Tengku Abdul Hamid, Tengku Haziyamin; Ezani, Ezureen; Khan Chowdhury, Ahmed Jalal (2010)
Lactic acid bacteria (LAB) are important inhabitants of animal intestine and are useful source of probiotic microorganism. Non-roiler chicken could be an ideal source of probiotic that can be utilized in large scale feeding of broiler chicken. In this study, fifty (50) bacterial strains that were randomly isolated from the gastrointestinal tract of non-broiler chicken (Gallus gallus) prepared in 5 ml of Phosphate Buffered Saline (PBS) were tested for the identification of LAB. LAB was identified by morphological and biochemical tests. Out of the fifty (50) isolates, eleven (11) isolates were Gram-positive cocci. The eleven (11) isolates have the ability to utilize lactose as part of their metabolism process and all showed negative reactions towards catalase test. The identified strains were then screened for their inhibitory effects against pathogenic bacteria by the disc diffusion method. Eleven (11) strains of LAB isolated produced antimicrobial compounds that were active against pathogenic bacteria especially Salmonella typhimurium strains. The disc dipped in broth containing LAB inhibited the growth of pathogenic bacteria by creating an inhibition zone around the disc. With all these tests, LAB were successfully isolated and screened from gastrointestinal tract of non-broiler chicken for potential probiotic purposes.